The Role of Families in Decisions about Cancer Treatments - Hobbs, Gabriela S. (Cancer, 2015)
BACKGROUND: Shared decision-making is an important component of patient-centered care and is associated with improved outcomes. Little is known about the extent and predictors of patient involvement of their family in decisions about cancer treatments. METHODS: The Cancer Care Outcomes Research and Surveillance (CanCORS) study is a large multi-regional prospective cohort study of cancer care and outcomes of lung and colorectal cancer patients. Participants reported the roles of their families in decisions about treatment. We used multinomial logistic regression to assess patient factors associated with family roles in decisions. RESULTS: Among 5284 patients, 80 (1.5%) reported family controlled decisions, with highest adjusted rates (12.8%) among non-English-speaking Asians. Among the 5204 remaining patients, 49.4% reported equally sharing decisions with family, 22.1% reported some family input, and 28.5% reported little family input. In adjusted analyses, married, female, older, and insured patients more often reported equally-shared decisions with family (all P<0.001). Adjusted family involvement varied by race/ethnicity and language, with Chinese-speaking Asian (59.8%) and Spanish-speaking Hispanic (54.8%) patients equally sharing decisions with family more often than whites (47.6%). Veterans Affairs patients were least likely to report sharing decisions with family, even after adjustment for marital status and social support (P<.001). CONCLUSIONS: Most newly diagnosed lung or colorectal cancer patients involve family members in treatment decisions. Non-English speaking Asians and Hispanics rely significantly on family. Further studies are needed to determine the impact of family involvement in treatment decisions on outcomes; until then, physicians should consider eliciting patients’ preferences for family involvement.